Unveiling neurogenic biomarkers for the differentiation between sepsis patients with or without encephalopathy: an updated meta-analysis - Jiyun Hu; Wenchao Li; Shucai Xie; Ya Liao; Tao Chen; Xinrun Wang; Weiping Xia; Fang Huang; Zhaoxin Qian; Lina Zhang (Systematic Reviews)
Abstract Background Sepsis-associated encephalopathy (SAE) is characterized by brain dysfunction in the context of sepsis and frequently leads to significant cognitive and neurological impairments, as well as an elevated risk of mortality. Accurate diagnosis of SAE is crucial for the timely initiation of optimal treatment and appropriate patient management. Neurogenic biomarkers hold promise as reliable serum diagnostic tools for the detection and longitudinal monitoring of SAE. This meta-analysis seeks to evaluate the diagnostic and prognostic utility of serum neurogenic biomarkers in patients with SAE. Methods The study protocol was registered in the PROSPERO database (CRD42023408312) and conformed to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. A meta-analysis was conducted to comprehensively and critically evaluate the existing body of evidence regarding the use of serum neurogenic biomarkers: neuron-specific enolase (NSE), ubiquitin C-terminal hydrolase-L1 (UCH-L1), Tau, S100 calcium-binding protein β (S100β), and glial fibrillary acidic protein (GFAP) for the diagnosis and risk assessment of fatality in SAE. We conducted a systematic search of electronic bibliographic databases, including PubMed, Web of Science, Embase, Cochrane databases, CNKI, CQVIP, and WFSD. The quality and risk of bias of the selected studies were assessed using the QUADAS-2 tool. For biomarkers reported in two or more studies, pooled standardized mean differences and 95% confidence intervals were calculated. Heterogeneity among the included studies was examined using the I 2 statistic and random-effects model was applied owing to large heterogeneity. Results Forty-two studies were included in our meta-analysis. The levels of serum neurogenic biomarkers were significantly higher in patients with SAE as compared to septic patients with no-encephalopathy (NE): NSE (standardized mean difference (SMD) 1.98 (95% CI 1.55–2.42), P < 0.00001); UCH-L1 (SMD 1.75 (95% CI 0.90–2.59), P < 0.0001); Tau (SMD 1.14 (95% CI 1.01–1.28), P < 0.00001); S100β (SMD 1.82 (95% CI 1.45–2.19), P < 0.00001); and GFAP (SMD 3.63 (95% CI 1.85–5.41), P < 0.0001). In addition, significantly lower serum neurogenic biomarkers levels were noted in septic patients with survivors as compared to non-survivors: NSE (SMD − 1.87 (95% CI − 2.43 to − 1.32), P < 0.00001); UCH-L1 (SMD − 1. 71 (95% CI − 2.24 to − 1.19), P < 0.00001); Tau (SMD − 0.57 (95% CI − 0.79 to − 0.35), P < 0.00001); S100β (SMD − 1.34 (95% CI − 1.88 to − 0.80), P < 0.00001). However, no significant differences in serum GFAP levels [SMD -7.98 (95% CI − 22.23–6.27), P = 0.27) were found between the surviving and non-surviving groups. Conclusion The increased serum neurogenic biomarkers may be predictive of SAE and mortality for septic patients, which are expected to be applied as a reliable blood-based diagnostic tool for detection and longitudinal monitoring in SAE patients. However, results should be interpreted with caution due to the high heterogeneity among studies.